Potential for use of accelerometers to monitor green sturgeon Acipenser medirostris (Ayres, 1854) behavior after handling. (4th December 2017) - Moser, M. L.; Corbett, S. C.; Burke, B. J.; Langness, O. P.
Summary: A pilot study was conducted to test the use of accelerometer tags (coded acoustic transmitters equipped with inertial sensors) to detect changes in green sturgeon activity following gillnet capture and release. Green sturgeon Acipenser medirostris (Ayres, 1854) is listed as threatened under the Endangered Species Act, but is captured as bycatch in both estuarine and coastal gillnet and trawl fisheries. Measured were tailbeat activity and swimming depth of sturgeon (145‐167 cm fork length) caught with gillnets in Willapa Bay, Washington during late July 2011. These data were transmitted acoustically over a period of up to 55 d to an array of 16 receivers positioned in the bay. Transmitters were either surgically implanted ( n  = 2) or attached externally to the dorsal scutes ( n  = 2). In spite of the small number of fish tagged, over 4, 800 data transmissions were obtained, with three fish detected over more than 46 d and in estuaries up to 55 km from the release site. Breakpoint regression analysis indicated that the accelerometers could be used to document discrete changes in activity of the fish after handling. Use of this technology could therefore allow the identification of fishing methods that are most harmful to protected species.